Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To find the remainder when the polynomial [tex]\( f(x) = x^3 + 5x^2 - 32x - 7 \)[/tex] is divided by [tex]\( x - 4 \)[/tex], we can use the Remainder Theorem. The Remainder Theorem states that the remainder of the division of a polynomial [tex]\( f(x) \)[/tex] by a linear divisor [tex]\( x - c \)[/tex] is [tex]\( f(c) \)[/tex].
In this case, our polynomial is [tex]\( f(x) \)[/tex] and our divisor is [tex]\( x - 4 \)[/tex]. Therefore, we need to find [tex]\( f(4) \)[/tex].
Let's evaluate [tex]\( f(4) \)[/tex]:
1. Start with the given polynomial:
[tex]\[ f(x) = x^3 + 5x^2 - 32x - 7 \][/tex]
2. Substitute [tex]\( x = 4 \)[/tex] into the polynomial:
[tex]\[ f(4) = (4)^3 + 5(4)^2 - 32(4) - 7 \][/tex]
3. Calculate each term:
- [tex]\( (4)^3 = 64 \)[/tex]
- [tex]\( 5(4)^2 = 5 \times 16 = 80 \)[/tex]
- [tex]\( 32(4) = 128 \)[/tex]
4. Substitute these values back into the expression:
[tex]\[ f(4) = 64 + 80 - 128 - 7 \][/tex]
5. Simplify the expression step by step:
- [tex]\( 64 + 80 = 144 \)[/tex]
- [tex]\( 144 - 128 = 16 \)[/tex]
- [tex]\( 16 - 7 = 9 \)[/tex]
Thus, the remainder when [tex]\( f(x) = x^3 + 5x^2 - 32x - 7 \)[/tex] is divided by [tex]\( x - 4 \)[/tex] is
[tex]\[ \boxed{9} \][/tex]
In this case, our polynomial is [tex]\( f(x) \)[/tex] and our divisor is [tex]\( x - 4 \)[/tex]. Therefore, we need to find [tex]\( f(4) \)[/tex].
Let's evaluate [tex]\( f(4) \)[/tex]:
1. Start with the given polynomial:
[tex]\[ f(x) = x^3 + 5x^2 - 32x - 7 \][/tex]
2. Substitute [tex]\( x = 4 \)[/tex] into the polynomial:
[tex]\[ f(4) = (4)^3 + 5(4)^2 - 32(4) - 7 \][/tex]
3. Calculate each term:
- [tex]\( (4)^3 = 64 \)[/tex]
- [tex]\( 5(4)^2 = 5 \times 16 = 80 \)[/tex]
- [tex]\( 32(4) = 128 \)[/tex]
4. Substitute these values back into the expression:
[tex]\[ f(4) = 64 + 80 - 128 - 7 \][/tex]
5. Simplify the expression step by step:
- [tex]\( 64 + 80 = 144 \)[/tex]
- [tex]\( 144 - 128 = 16 \)[/tex]
- [tex]\( 16 - 7 = 9 \)[/tex]
Thus, the remainder when [tex]\( f(x) = x^3 + 5x^2 - 32x - 7 \)[/tex] is divided by [tex]\( x - 4 \)[/tex] is
[tex]\[ \boxed{9} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.